Analysis of goal scoring patterns in the 2012 European Football Championship - Mitrotasios, M.; Armatas, V. (The Sport Journal, 2014)
Purpose: The aim of the present study was to investigate the factors associated with goal scoring in top class football matches. Methods: 76 goals analyzed from 31 matches from the European football Championship in Poland-Ukraine in 2012. The SportScout performance analysis tool was used to time code when goal scored and the associated behaviors relating to goal scoring. Results: It was presented that 57.9 % of the goals were scored in the second half and most of them in the last 15-min period, while the first goal seems to play an important role in the final result of the match. Most goals were scored during open play (72.4%) but 27.6% scored after a set play, mainly following corner kick and free kick. Concerning initiation zone of the attack, it was presented that 56.6% began from the attacking half. Most goals were scored after a cross (43.7%) while regarding goal scoring area, over 90% of goals were scored inside the penalty area and specifically from the area between penalty spot and goal zone (42.1%). Finally, almost ½ of goals were scored without any pressure from defenders. Conclusions: The present study presented guidelines to coaches in order to design trainings similar to the actual competition and adapt the game style with regard to match status. Moreover, coaches can use this information to establish objectives for players and teams with a special reference to the offensive or defensive play.